Investigation on daily or every three days supplementation with protein or protein and starch of cattle fed tropical grass - Reis, William Lima Santiago dos (2018)
Effects of daily or every three days supplementation with protein or protein and starch on intake, digestion, rumen dynamics, urinary excretion characteristics, nitrogen (N) balance and liver function of Nellore heifers fed high-quality tropical forage were evaluated. Five Nellore heifers (299 ±7.5 kg of body weight, BW) fitted with ruminal and abomasal cannulas were used in a 5 x 5 Latin square design. Treatments included: control, non- supplemented; 200 g of crude protein (CP) daily; 200 g of CP and 400 g of starch daily; 600 g of CP every three days; 600 g of CP and 1200 g of starch every three days. Therefore, over a three-day supplementation cycle, on average, supplemented animals received 200 of CP, or 200 g of CP plus 400 g of starch. Supplements, on average, enhanced (P<0.02) CP intake, digested organic matter (DOM) intake and the ratio of CP intake to DOM intake (CP:DOM ) when comparing to control. Among supplemented animals, every three days (infrequent) supplementation decreased (P<0.05) forage intake and therefore the intake of several fractions of the diet. Starch addition to supplements also had a negative effect on forage intake, noted as a decrease(P<0.04) on NDF intake (g/kg BW). Supplements enhanced (P<0.01) total organic Matter (OM) and CP digestibility. Ruminal CP digestibility was also enhanced (P<0.01) by supplements, changing from negative in control to positive in supplemented animals. The same pattern was observed for rumen N balance (RNB). In situ degradability of potentially digestible NDF (pdNDF), on average of the three-day supplementation cycle, was not affected (P≥0.26) by any treatment. However, there was (P<0.02) an interaction between days of the supplementation cycle and treatments. Control and frequently supplemented animals presented stable in situ rate of fiber digestion throughout the three-day supplementation cycle. Nevertheless, for animals supplemented with protein and starch every three days, there was an impairment to fiber digestion on the first day of the supplementation cycle (day 1), day in which these animals had access to supplements, followed by a recuperation of fiber digestion rate in the following two days (day 2 and day3), when they were not supplemented. Furthermore, for animals supplemented with protein every three days, inversely, in situ fiber digestion rate was greater on day 1 and then gradually dropped in the day 2 and day 3, following rumen ammonia N (RAN) pattern observed in these animals. On average, supplements enhanced (P<0.01) RAN from 4,2 to 8,7 mg/dL, respectively, for control and supplemented. Among supplemented animals, infrequent supplementation enhanced (P<0.04) RAN level when compared to daily supplementation. An interaction (P<0.01) between days of the supplementation cycle and treatments pointed out that RAN levels were constant over days for control and frequently supplemented animals, but for infrequent supplemented animals it was greater on day 1 and then decreased in the two following days reaching, on day 3, values similar those ones observed for control. Supplementation did not (P≥0.21) affected pH or volatile fat acids concentration in rumen fluid when compared to control, but among supplemented animals, infrequent supplementation reduced (P<0.02) acetate-to-propionate ratio and starch addition reduced (P<0.02) acetic molar proportion. Supplements promoted an 90% increment in N balance. It raised from 8 (control) to 15 g/day (supplemented). Among supplemented animals, there was no (P≥0.43) differences in N balance. Microbial flow and microbial production efficiency were not affected (P≥0.18) by treatments. On average, supplemented animals presented greater (P<0.01) Urinary-N excretion (UNE) than control. Supplements, on average, also enhanced (P<0.01) serum urea-N (SUN). Among supplemented animals, addition of starch to supplements reduced (P<0.04) UNE, but it did not result in greater N retention. There was (P<0.01) an interaction between days of the supplementation cycle and treatments for SUN and the urinary excretion characteristics. Non-supplemented and daily supplemented animals presented constant values for these variables among the three-day supplementation cycle. However, in animals supplemented every three days changes in SUN levels resulted in an untypical decoupling between SUN and RAN throughout the supplementation cycle. While RAN was decreasing between day 1 and day 2, SUN peaked on day 2, which seem to be supported by the greater salvage of the urea-N filtered in kidneys, on day 2. In other words, the changes in SUN and urinary excretion characteristics pointed out that the they after supplementation seem to be important for N saving in ruminants infrequently supplemented. The greater N retention of supplemented animals was associated with greater (P<0.02) blood concentrations of IGF-1, and Insulin. Liver function, accessed through dousing transaminases activities in blood, was not affected (P≥0.07) by treatments. In summary, Animals supplemented have greater N balance than non- supplemented animals. Starch addition to protein supplements does not enhance N balance. In spite of no changes in N balance between supplemented animals, animals receiving different supplements applied distinct mechanisms, in regard of N transactions along rumen, blood and kidneys.